Barriers constraining management innovation (MI) adoption in the Ghanaian construction consulting sector: A case study. Issue 4 (5th October 2015) - Owusu-Manu, D.; Quaigrain, R.; Edwards, D.J.
Abstract : Purpose: – The purpose of this paper is to critically examine and report upon the barriers that constrain MI within the Ghanaian construction consulting sector. Globalization and the shift towards knowledge-based economies have encouraged organizations to adopt management innovation (MI) as a means of increasing market share and creating competitive leverage. Organizations within developing countries, such as Ghana, have followed this global trend, but barriers continue to affect MI adoption. Design/methodology/approach: – The research is positioned within a mixed methods "deductive" methodological tradition and is undertaken via a three-stage iterative approach. First, the research synthesizes relevant literature to identify 14 potential barriers to MI adoption. Second, using convenient and snowball sampling techniques, structured survey questionnaires were distributed to 70 consulting firms within the Kumasi metropolis; a high 78.5 per cent response rate was returned. Third, data were analyzed using descriptive statistics and principal component (factor) analysis to determine underlying barriers that restrict MI adoption. Findings: – The barriers to MI adoption are contained within four inextricably linked factor groups: organizational structural influences, flow of information, institutional constraints and costs of innovations. The findings demonstrate that innovation thrives in an organizational environment that nurtures creativity, staff development, moderate risk taking and idea generation and management – albeit, the external economic environment must also be conducive to facilitating innovation within companies and organizations. Practical implications: – Innovation within construction companies is a prerequisite requirement for a dynamic and competitive economy because it nurtures self-regulating "free market" behavior, which creates considerable benefit to an economy. Such an attribute is particularly attractive for the developing country of Ghana, which has historically suffered from recurrent social, political and economic pressures. Hence, the research findings will be of practical interest to policymakers, academics and industrialists who have a vested interest in improving the performance of the Ghanaian economy. It will also be of interest to others within developing countries who are experiencing similar issues. Originality/value: – This research work builds upon the work of previous scholars in this field and investigates the barriers to implementing MI in Ghana. The paper's findings will be useful to organizations and government policymakers who seek to increase business performance within a free market and profitability in an ever increasingly competitive world.